2019
DOI: 10.3389/fphys.2019.01413
|View full text |Cite
|
Sign up to set email alerts
|

Match and Training Load Exposure and Time-Loss Incidence in Elite Rugby Union Players

Abstract: ObjectiveTo investigate the impact of match and training load on time-loss incidence in elite, professional Rugby Union players.Materials and MethodsEighty-nine Rugby Union players were monitored over two seasons of training and competition. Load was measured for all training sessions and matches using subjective [session ratings of perceived exertion (sRPE) load; RPE × session duration] and objective [global positioning systems (GPS); distance and high-speed running distance] methods and quantified using mult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 32 publications
0
9
0
Order By: Relevance
“…Body load data showed high levels of G force are sustained during tackling and scrummaging. Cousins et al [ 66 ] 89 professional rugby union players from the top two leagues in England. STATSport Apex Data were collected from two GPS tracking devices (5 and 10 Hz) over 2 seasons.…”
Section: Resultsmentioning
confidence: 99%
“…Body load data showed high levels of G force are sustained during tackling and scrummaging. Cousins et al [ 66 ] 89 professional rugby union players from the top two leagues in England. STATSport Apex Data were collected from two GPS tracking devices (5 and 10 Hz) over 2 seasons.…”
Section: Resultsmentioning
confidence: 99%
“…In rugby union, the risk of injury is high compared with that of other team sports (81 per 1000 match hours [16]) and therefore modifiable risk factors such as training load offer a potentially useful method for injury risk mitigation. While little evidence exists in rugby union as to the utility of the ACWR [17,18], establishing the extent to which methodological parameters could be influencing the link between the ACWR and injury risk in this setting is prudent. Importantly, it is well established that injury etiology is multifactorial in nature [19], and therefore when examining the link between training load and injury, other well known risk factors must be considered.…”
Section: Training Load and Injury Risk In Elite Rugby Union: The Largmentioning
confidence: 99%
“…Only two studies [34,42] included in this review used the EWMA model and suggested that the EWMA model was a better alternative to rolling averages for assessing injury risk. Some studies show that while both models demonstrate significant associations between ACWR and injury risk [49][50][51], rolling ACWRs may underestimate the injury risk at higher ACWR ranges [49,50,52,53], while others suggest that there are no differences between the rolling averages and the EWMA methods [51]. Studies included in this review support both methods, but when directly compared, the EWMA model shows greater sensitivity.…”
Section: How To Best Calculate the Acwr? The Decision Requires Contextmentioning
confidence: 79%